M&A successes: Breadth, depth, and deal completion time in the US semiconductor industry - Taewoo Roh; Jieun Hwang; Byung Il Park (BRQ Business Research Quarterly, 2023)
Most previous studies examining M&As (mergers and acquisitions) have focused on the post-merger integration process. While there have been studies that have partially investigated the importance of deal completion, we argue that firms could learn to increase their deal completions by leveraging their experience from prior successful acquisitions and that their cumulative success could reduce the deal completion time; that is, the time from the announcement of the deal to its resolution. To address this unexplored issue about M&As, we investigated whether prior intra- and/or inter-industry acquisition experiences helped accelerate subsequent focal acquisitions in the semiconductor industry, which is characterized by rapid technological innovation. We tested our hypotheses on data consisting of 323 acquisition deals in the US semiconductor industry between 2000 and 2013. The results showed that both prior intra- and inter-industry acquisition experiences significantly reduced deal completion time.
Keywords: M10; 650; Deal completion time; intra-industry acquisition; inter-industry acquisition; M&A experience; semiconductor industry